2011
DOI: 10.1371/journal.pone.0020120
|View full text |Cite
|
Sign up to set email alerts
|

Harnessing Expression Data to Identify Novel Candidate Genes in Polycystic Ovary Syndrome

Abstract: Novel pathways in polycystic ovary syndrome (PCOS) are being identified in gene expression studies in PCOS tissues; such pathways may contain key genes in disease etiology. Previous expression studies identified both dickkopf homolog 1 (DKK1) and DnaJ (Hsp40) homolog, subfamily B, member 1 (DNAJB1) as differentially expressed in PCOS tissue, implicating them as candidates for PCOS susceptibility. To test this, we genotyped a discovery cohort of 335 PCOS cases and 198 healthy controls for three DKK1 single nucl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“…Polycystic ovary syndrome (PCOS) characterized by chronic ovulatory dysfunction, hyperandrogenism, polycystic ovary morphology, obesity and insulin resistance is a common endocrine disorder affecting 5–10% of women of reproductive age 1 . Many studies suggest that the genetic factors play an important role in the aetiology of PCOS 2 . Those have been analysed in searching for the molecular basis of PCOS, such as genes involved in steroid hormone biosynthesis (CYP11a, CYP17 and CYP19), 3,4 genes involved in gonadotropin action (LHR and FSHR), 5 genes involved in the insulin signalling pathway (TRB3 and IRS‐1/2) 6,7 and genes involved in insulin receptor (INSR) gene 8…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Polycystic ovary syndrome (PCOS) characterized by chronic ovulatory dysfunction, hyperandrogenism, polycystic ovary morphology, obesity and insulin resistance is a common endocrine disorder affecting 5–10% of women of reproductive age 1 . Many studies suggest that the genetic factors play an important role in the aetiology of PCOS 2 . Those have been analysed in searching for the molecular basis of PCOS, such as genes involved in steroid hormone biosynthesis (CYP11a, CYP17 and CYP19), 3,4 genes involved in gonadotropin action (LHR and FSHR), 5 genes involved in the insulin signalling pathway (TRB3 and IRS‐1/2) 6,7 and genes involved in insulin receptor (INSR) gene 8…”
Section: Introductionmentioning
confidence: 99%
“…1 Many studies suggest that the genetic factors play an important role in the aetiology of PCOS. 2 Those have been analysed in searching for the molecular basis of PCOS, such as genes involved in steroid hormone biosynthesis (CYP11a, CYP17 and CYP19), 3,4 genes involved in gonadotropin action (LHR and FSHR), 5 genes involved in the insulin signalling pathway (TRB3 and IRS-1/2) 6,7 and genes involved in insulin receptor (INSR) gene. 8 As PCOS is associated with a 2-7-fold increased risk to develop impaired glucose tolerance (IGT) or type 2 diabetes mellitus (T2DM), genes related to T2DM may also play a role in PCOS pathogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…DNAJB1, one of the genes they identified as over-expressed among high male responders following 6 weeks of aerobic training, was also significantly over-expressed in mRNA collected at baseline among high responders to the GEAR exercise protocol. DNAJB1 is an androgen protein co-chaperone in the glucocorticoid receptor signalling (Jones, 2011) that is under transcriptional regulation by insulin (Goodall et al, 2010). Two genes (CTTN, PRKAR2B) were also over-expressed (FDR < 0.10) in baseline mRNA levels among the women who were subsequently categorized as "high" versus "low" responders.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have identified that DKK1 and DNAJB1 are differentially expressed in PCOS tissue [76]. Thus, DKK1 (encoding a dickkopf related protein) and DNAJB1 (encoding DnaJ or Hsp40 homolog) are potential genes of interest in the pathogenesis of PCOS.…”
Section: Polycystic Ovarian Syndrome (Pcos)mentioning
confidence: 99%